2018
DOI: 10.1038/s41467-018-04120-z
|View full text |Cite|
|
Sign up to set email alerts
|

C/EBPβ regulates delta-secretase expression and mediates pathogenesis in mouse models of Alzheimer’s disease

Abstract: Delta-secretase cleaves both APP and Tau to mediate the formation of amyloid plaques and neurofibrillary tangle in Alzheimer’s disease (AD). However, how aging contributes to an increase in delta-secretase expression and AD pathologies remains unclear. Here we show that a CCAAT-enhancer-binding protein (C/EBPβ), an inflammation-regulated transcription factor, acts as a key age-dependent effector elevating both delta-secretase (AEP) and inflammatory cytokines expression in mediating pathogenesis in AD mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 50 publications
6
87
0
Order By: Relevance
“…MAO-A generates H 2 O 2 and DOPEGAL, when it metabolizes NE. Both H 2 O 2 and DOPEGAL induce AEP activation and trigger cell death, and we have shown that the transcription factor, CEBP-β, regulates the expression of AEP (40). Conceivably, there is positive feedback between NE metabolism and CEBP-β, whereby increased levels of MAO-A and H 2 O 2 activate CEBP-β, which, in turn, induces further MAO-A and AEP expression.…”
Section: Discussionmentioning
confidence: 82%
“…MAO-A generates H 2 O 2 and DOPEGAL, when it metabolizes NE. Both H 2 O 2 and DOPEGAL induce AEP activation and trigger cell death, and we have shown that the transcription factor, CEBP-β, regulates the expression of AEP (40). Conceivably, there is positive feedback between NE metabolism and CEBP-β, whereby increased levels of MAO-A and H 2 O 2 activate CEBP-β, which, in turn, induces further MAO-A and AEP expression.…”
Section: Discussionmentioning
confidence: 82%
“…In the brain, these changes are sugges-tive of age-related induction of neuro-inflammation and activation of glia. C/EBPb (coded by the Cebpb gene) is a basicleucine zipper DNA-binding protein that controls expression of cytokines and other pro-inflammatory genes and induces pathways that are critical for glia activation (Bradley et al, 2003;Wang et al, 2018). Apart from being implicated in neuro-inflammation, C/EBPb controls expression of delta-secretase enzyme, which is thought to contribute to the pathology in Alzheimer's disease by cleaving both Tau and beta-amyloid precursor protein .…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, these changes are suggestive of age-related induction of neuro-inflammation and activation of glia. C/EBPβ (coded by the Cebpb gene) is a basic-leucine zipper DNA-binding protein that controls expression of cytokines and other pro-inflammatory genes, and induces pathways that are critical for glia activation (Bradley et al, 2003; Wang et al, 2018). Apart from being implicated in neuro-inflammation, C/EBPβ controls expression of delta-secretase enzyme, which is thought to contribute to the pathology in Alzheimer’s disease by cleaving both Tau and beta-amyloid precursor protein (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPβ (coded by the Cebpb gene) is a basic-leucine zipper DNA-binding protein that controls expression of cytokines and other pro-inflammatory genes, and induces pathways that are critical for glia activation (Bradley et al, 2003; Wang et al, 2018). Apart from being implicated in neuro-inflammation, C/EBPβ controls expression of delta-secretase enzyme, which is thought to contribute to the pathology in Alzheimer’s disease by cleaving both Tau and beta-amyloid precursor protein (Wang et al, 2018). ISG15 (interferon stimulated gene 15) (Kessler et al, 1988), which also was upregulated in every tissue examined, is a ubiquitin-like protein, and its expression is induced by type-I IFNs and by p53 (Huang and Bulavin, 2014) (Park et al, 2016).…”
Section: Discussionmentioning
confidence: 99%